El emprendimiento femenino: un estudio multi-caso de factores críticos en el noreste de México (Female entrepreneurship: a multi-case study of critical factors in Northeastern Mexico) - Briseño, Olivia; Briseño, Arturo; Lira Arjona, Alfonso López (Imprenta Universitaria de la Universidad Autónoma de Nuevo León, 2016)
Abstract. Women entrepreneurs represent a research phenomenon that has increased its importance over the last years. This study contributes to understand the role of women entrepreneurs in developing countries. In particular, we study the factors that influence the entrepreneurial activity of women in Mexico, identifying the characteristics both from the business and the entrepreneur, along with the barriers and impact of her entrepreneurial activity. Three case studies are analyzed from Tamaulipas, Mexico. The main finding of this study is that the context in which the women entrepreneur is immersed is essential to interpret her activity, being age an important factor influencing the perception of the entrepreneurial activity.